Effects of lysine-to-glycine mutations in the ATP-binding consensus sequences in the AddA and AddB subunits on the Bacillus subtilis AddAB enzyme activities. - Haijema, B J (1996)
The N-terminal regions of both subunits AddA and AddB of the Bacillus subtilis AddAB enzyme contain amino acid sequences, designated motif I, which are commonly found in ATP-binding enzymes. The functional significance of the motif I regions was studied by replacing the highly conserved lysine residues of the regions in both subunits by glycines and by examination of the resulting mutant enzymes with respect to their enzymatic properties. This study shows that the mutation in subunit AddB hardly affected the ATPase, helicase, and exonuclease activities of the AddAB enzyme. However, the mutation in subunit AddA drastically reduced these activities, as well as the kcat for ATP hydrolysis. The apparent Km for ATP in ATP hydrolysis did not significantly deviate from that of the wild-type enzyme. These results suggest that the lysine residue in motif I of subunit AddA of the AddAB enzyme is not essential for the binding of the nucleotide but has a role in ATP hydrolysis, which is required for the exonuclease and helicase activities of the enzyme.